Superconducting Quantum Metamaterials from Convergence of Soft and Hard Condensed Matter Science. Issue 26 (16th May 2021) - Beaucage, Peter A.; van Dover, R. Bruce; DiSalvo, Francis J.; Gruner, Sol M.; Wiesner, Ulrich
Abstract: Superconducting quantum metamaterials are expected to exhibit a variety of novel properties, but have been a major challenge to prepare as a result of the lack of appropriate synthetic routes to high‐quality materials. Here, the discovery of synthesis routes to block copolymer (BCP) self‐assembly‐directed niobium nitrides and carbonitrides is described. The resulting materials exhibit unusual structure retention even at temperatures as high as 1000 °C and resulting critical temperature, T c, values comparable to their bulk analogues. Applying the concepts of soft matter self‐assembly, it is demonstrated that a series of four different BCP‐directed mesostructured superconductors are accessible from a single triblock terpolymer. Resulting materials display a mesostructure‐dependent T c without substantial variation of the XRD‐measured lattice parameters. Finally, field‐dependent magnetization measurements of a sample with double‐gyroid morphology show abrupt jumps comparable in overall behavior to flux avalanches. Results suggest a fruitful convergence of soft and hard condensed matter science. Abstract : Superconducting mesostructured niobium carbonitrides with different morphologies are prepared from a single block copolymer via self‐assembly using a variety of new synthetic routes. Superconducting transition temperatures are comparable to bulk analogues but vary with mesostructure, a typical fingerprint of metamaterials, while some materials exhibit atypical flux avalanches. The results suggest a fruitful convergence of soft and hard condensed matter science.